Transparansi Pelayanan Publik Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu (DPMPTSP) - Andri Irawan (Universitas Islam Darul Ulum Lamongan, 2018)
Transparency refers to a situation in which all aspects of the service delivery process are open and can be easily identified by users. This study aims to describe and analyze the transparency of services at the Merauke Regency Investment and One-Stop Service using a qualitative approach. The results of the analysis show that indicators of transparency in general have not shown maximum results. This can be seen from the indicators of the openness of the service process and the ease of obtaining information that has not been fully carried out transparently. The unclear service procedures and lack of explanation of the service procedures also resulted in the community waiting, and would lead to misunderstandings between service providers and recipient communities. Whereas for the complaints mechanism a special field has been established which handles public complaints but a suggestion box has not been provided as a facility to receive complaints. Factors that hamper transparency are human resources factors that are still lacking in quantity and quality, factors of Facilities and Infrastructure that are still inadequate as one-stop integrated service agencies, and technological factors, namely service applications that are still not perfect.